Mental disorders, suicide attempt and suicide: differences in the association in refugees compared with Swedish-born individuals. (December 2020) - Björkenstam, Emma; Helgesson, Magnus; Amin, Ridwanul; Mittendorfer-Rutz, Ellenor
Abstract : Background: Mental disorders are associated with an elevated risk for suicide attempt and suicide. Whether the strength of the associations also holds for refugees is unclear. Aims: To examine the relationship between specific mental disorders and suicide attempt and suicide in refugees and Swedish-born individuals. Method: This longitudinal cohort study included 5 083 447 individuals aged 16–64 years, residing in Sweden in 2004, where 196 757 were refugees. Mental disorders were defined as having a diagnosis in psychiatric care during 2000–2004. Estimates of risk of suicide attempt and suicide were calculated as hazard ratios with 95% confidence intervals. Adjustments were made for important confounding factors, including history of attempt. The reference group comprised Swedish-born individuals without mental disorders. Results: Rates for suicide attempt in individuals with a mental disorder were lower in refugees compared with Swedish-born individuals (480 v. 850 per 100 000 person-years, respectively). This pattern was true for most specific disorders: compared with the reference group, among refugees, multivariable-adjusted hazard ratios for suicide attempt ranged from 3.0 (anxiety) to 7.4 (substance misuse), and among Swedish-born individuals, from 4.9 (stress-related disorder) to 9.3 (substance misuse). For schizophrenia, bipolar disorder and personality disorder, estimates for suicide attempt were comparable between refugees and Swedish-born individuals. Similar patterns were seen for suicide. Conclusions: For most mental disorders, refugees were less likely to be admitted to hospital for suicide attempt or die by suicide compared with Swedish-born individuals. Further research on risk and protective factors for suicide attempt and suicide among refugees with mental disorders is warranted. Declaration of interest: None.